40 likes | 237 Views
( axb ) m = a m b m. Lesson 6. How does it work?. This is the same as the previous rule, because one index number is inside brackets and the other is outside the indices are multiplied together. ( axb ) m =(a 1 x b 1 ) m = a 1xm xb 1xm = a m b m. Example. ( axb ) m = a m b m
E N D
(axb)m=ambm Lesson 6
How does it work? • This is the same as the previous rule, because one index number is inside brackets and the other is outside the indices are multiplied together. (axb)m =(a1 xb1)m = a1xmxb1xm = ambm
Example (axb)m=ambm (7xb)9 =79b9 • This all the working which is required for this task. Remember that both numbers need to be multiplied.